In your dreams - Morgan, Sally, 1951 January 18-; Bancroft, Bronwyn (South Fremantle, Western Australia : Sandcastle Books, 1997)
A grandmother helps her granddaughter interpret her dreams. Aboriginal story.
White
Children.
Keywords: Grandmothers -- Juvenile fiction; Art, Aboriginal Australian -- Juvenile fiction; Dream interpretation -- Juvenile fiction; Dreams -- Juvenile fiction; Aboriginal Australians -- Juvenile fiction; Australian; Children's stories